2023
DOI: 10.4028/p-h9p342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mn Incorporated into LiNbO<sub>3</sub> Crystal Structure on the Electronic and Optical Properties Using First-Principles Study

Abstract: The structural, electronic and optical properties of lithium niobate (LiNbO3) and manganese (Mn)-doped LiNbO3 are investigated using a first-principles study. The first-principles calculation in this work is implemented using CASTEP computer code with GGA-PBE correlation. The band structure and density of states are calculated to analyze the effect of Mn doping on the electronic properties of LiNbO3. Hubbard U correction is applied to Nb 4d state with U= 11 eV and the corrected band gap obtained is 3.771 eV. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(24 reference statements)
1
0
0
Order By: Relevance
“…Zheng et al [ 38 ], Ait brahim [ 39 ] and Maarouf et al [ 12 ] reported a reduced in Fe-doped LNO and KNO, too. We also obtain this behavior for other TM ions with ionic radius smaller than that of Nb in qualitative agreement with the experimental data of Maarouf et al [ 12 ] for KNO and of Liang et al [ 14 ], Mamoun et al [ 40 ], and Zainuddin et al [ 41 ] for LNO. The results indicate that the band gap is significantly narrowed for all the transition metal-doped LNO and KNO.…”
Section: Resultssupporting
confidence: 91%
“…Zheng et al [ 38 ], Ait brahim [ 39 ] and Maarouf et al [ 12 ] reported a reduced in Fe-doped LNO and KNO, too. We also obtain this behavior for other TM ions with ionic radius smaller than that of Nb in qualitative agreement with the experimental data of Maarouf et al [ 12 ] for KNO and of Liang et al [ 14 ], Mamoun et al [ 40 ], and Zainuddin et al [ 41 ] for LNO. The results indicate that the band gap is significantly narrowed for all the transition metal-doped LNO and KNO.…”
Section: Resultssupporting
confidence: 91%